Neuroscience contributions to pedagogy: a necessary dialogue (Research, Society and Development, 2021)
This work aimed to analyze the contributions of neuroscience to the education of the pedagogue, as well as to verify how neuroscience can help in the improvement of pedagogical practices. Method: The present study was developed based on the exploratory method, considering the bibliographic research. For the selection of bibliographic material, the following databases were used: Medical Literature Analysis and Retrieval System on-line (MEDLINE) provided by PUBMED of the US National Library of Medicine National Institutes of Health, Latin American and Caribbean Literature in Sciences of the (LILACS) and Scientific Electronic Library Online (SCIELO). Through this research it was found that understanding the brain and its structures is fundamental for the development of educational methods through the dialogue between pedagogy and neuroscience. In everyday school practices, teachers face many challenges, including how to deal with students with learning disorders. Neuroscience can help to identify and overcome these difficulties, as well as lay the groundwork for evidence-based reform in the educational process.